High-strength and high-toughness soluble magnesium alloy and preparation method thereof
By using Al, Ni, Cu and other raw materials, homogenous denaturant and wetting liquid in soluble magnesium alloys, the problem of insufficient performance balance in the prior art is solved, and high strength and toughness and excellent bending resistance are achieved. Compressive resistance and maintain stable performance in humid and low temperature environments.
Patent Information
- Application Number
- CN202411037400.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-13
AI Technical Summary
Existing soluble magnesium alloys have shortcomings in performance balance, making it difficult to achieve coordinated optimization of performance, especially in terms of bending, compressive strength and toughness.
Al, Ni, and Cu are used as main agent raw materials, and the preparation method of homogenizing denaturant includes blending of Sn powder and Zr powder and ball milling of lanthanum-regulating homogenizer, combined with ultrasonic treatment of moisturizing liquid and thermal enhancement improvement Treatment to form a high-strength and tough soluble magnesium alloy.
The performance coordinated improvement of soluble magnesium alloys is achieved, improving the product's bending, compressive strength and toughness, while maintaining excellent bending strength and elongation performance in humid and low temperature environments.
Smart Images

Figure BDA0004971467660000111 
Figure BDA0004971467660000121 
Figure BDA0004971467660000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soluble magnesium alloys, and in particular to a high-strength and toughness soluble magnesium alloy and a preparation method thereof. Background Art
[0002] Soluble metal materials have been gradually applied to the horizontal well staged fracturing and exploitation process of shale oil and gas. The temporary plugging tools prepared with them can dissolve naturally in the groundwater environment, avoiding the manual removal process, which can significantly improve production efficiency and reduce costs.
[0003] Existing soluble magnesium alloys not only require excellent solubility and toughness, but also have high requirements for the bending and compressive strength of the product. The difficulty of the present invention lies in the performance balance of the product and the realization of coordinated performance optimization. Based on this, the present invention further improves it. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a high-strength and toughness soluble magnesium alloy and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a high-strength and toughness soluble magnesium alloy, comprising the following raw materials in weight percentage:
[0007] Al 2-4%, Ni 1.5-2.0%, Cu 1.5-2.0%, homogeneous modifier 2-4%, and the balance Mg.
[0008] Preferably, the preparation method of the homogenizing denaturant is:
[0009] S01: 2-5 parts of Sn powder and 1-3 parts of Zr powder are mixed, and then fully blended with 10-15 parts of sodium citrate solution to obtain a blended Sn-Zr agent;
[0010] S02: The blended Sn-Zr agent and the lanthanum-adjusted homogenizer are stirred and homogenized in a weight ratio of 5:2. After homogenization, the mixture is washed with water and dried to obtain a lanthanum homogenized modifier.
[0011] S03: The lanthanum homogeneous modifier is heat-treated at 175-185°C for 5-10 minutes, and then cooled to room temperature at a rate of 1-2°C / min to obtain a homogeneous denaturant.
[0012] Preferably, the mass fraction of the sodium citrate solution is 10-15%; the homogenizing speed of the stirring homogenizing treatment is 750-850 r / min, and the homogenizing time is 20-30 min.
[0013] Preferably, the preparation method of the lanthanum-regulated homogenizer is:
[0014] Add 3 to 5 parts of nano-silicon dioxide and 1 to 2 parts of ethanol solvent into 4 to 7 parts of sodium lignin sulfonate solution and mix thoroughly to obtain nano-silicon dioxide liquid;
[0015] 2-5 parts of nano-silica liquid, 3-4 parts of lanthanum nitrate solution, 1-2 parts of tetrabutyl titanate and 0.35-0.45 parts of nano-silica sol are ball-milled at a speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a lanthanum-adjusted homogenizer.
[0016] Preferably, the mass fraction of the sodium lignin sulfonate solution is 8-12%; the mass fraction of the lanthanum nitrate solution is 2-5%.
[0017] The present invention also provides a method for preparing a high-strength and toughness soluble magnesium alloy, comprising the following steps:
[0018] Step 1: Al, Ni, Cu and Mg are first smelted completely at 750°C, and then a homogenizing modifier is added and stirred and smelted for 25 to 30 minutes at a smelting speed of 450 to 500 r / min, and then argon is introduced for refining and degassing to obtain a smelt, which is poured into a mold to form an alloy ingot;
[0019] Step 2: The alloy ingot is placed in a lubricating liquid 3 to 5 times the volume of the alloy ingot for ultrasonic lubricity treatment. After the treatment, the ingot is washed with water and dried to obtain a body with improved wettability.
[0020] Step 3: The improved body of wettability is then subjected to a heat-enhanced improvement treatment, and after the treatment is completed, a heat-improved body is obtained;
[0021] Step 4: Extruding the heat-modified body to form the soluble magnesium alloy of the present invention, the extrusion temperature is 360° C., the extrusion ratio is 5-10, and the extrusion speed is 10 m / min.
[0022] Preferably, the specific operation steps of the heat enhancement improvement treatment are:
[0023] First, perform primary treatment at a temperature of 320-350°C for 10-20 minutes, then reduce the temperature to 210-220°C at a rate of 2-4°C / min for secondary treatment for 20-30 minutes, and finally cool to room temperature at a rate of 1-3°C / min.
[0024] Preferably, the ultrasonic power of the ultrasonic lubricity treatment is 350-400W, and the ultrasonic time is 20-30min.
[0025] Preferably, the preparation method of the lubricating liquid is:
[0026] S11: placing the carbon nanotubes in a proton irradiation box for 5 to 10 minutes, with an irradiation power of 350 W, and then putting them into standby mode after the irradiation is completed;
[0027] S12: Then, 4 to 7 parts of irradiated carbon nanotubes, 2 to 5 parts of yttrium nitrate solution, 1 to 3 parts of silane coupling agent KH560 and 2 to 5 parts of sodium dodecylbenzene sulfonate solution are mixed thoroughly to obtain a lubricating liquid.
[0028] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 10-15%.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The soluble magnesium alloy of the present invention uses Al, Ni, Cu and Mg as main raw materials. The raw materials are matched and coordinated with each other. A homogenizing modifier is added to cooperate with the preparation process of the present invention to obtain a soluble magnesium alloy product, which has solubility and toughness properties, and the bending and compressive strength of the product are improved in a coordinated manner.
[0031] 2. The homogenizing modifier is a mixture of Sn powder and Zr powder, and then dispersed and improved with sodium citrate solution. The formed blending system is then homogenized and adjusted with a lanthanum-adjusted homogenizer. The lanthanum-adjusted homogenizer is blended with nano-silicon dioxide and sodium lignin sulfonate solution to optimize the dispersion and activity of nano-silicon dioxide. Lanthanum nitrate solution, tetrabutyl titanate and nano-silica sol are then co-mixed and ball-milled. The raw materials are mutually harmonized and coordinated to enhance the interface and activity of nano-silicon dioxide. Thus, the lanthanum-adjusted homogenizer assists the blending of Sn-Zr agent, strengthens the alloy grains, and enhances the solubility, strength and toughness coordination of the product through the mutual assistance and synergy between the raw materials.
[0032] 3. The lubricating liquid uses carbon nanotubes after proton irradiation to optimize its activity performance, and then improves it by blending yttrium nitrate solution, silane coupling agent KH560 and sodium dodecylbenzene sulfonate solution, and undergoes ultrasonic lubricity treatment to optimize the interfacial activity of the alloy ingot. At the same time, the lubricating liquid formed by the blending of the raw materials and the homogenizing modifier are coordinated to enhance the performance of the product in the preparation process of the alloy;
[0033] 4. In the heat strengthening improvement treatment, the temperature of the first heat treatment is 320-350℃ for 10-20min, and then the temperature is reduced to 210-220℃ at a rate of 2-4℃ / min for secondary treatment. The secondary treatment time is 20-30min, and finally the temperature is cooled to room temperature at a rate of 1-3℃ / min to further optimize the grain structure. At the same time, the performance of the product is further enhanced by the coordinated improvement treatment of the lubricating liquid. DETAILED DESCRIPTION
[0034] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] A high-strength and toughness soluble magnesium alloy of this embodiment includes the following raw materials in weight percentage:
[0036] Al 2-4%, Ni 1.5-2.0%, Cu 1.5-2.0%, homogeneous modifier 2-4%, and the balance Mg.
[0037] The preparation method of the homogeneous denaturant of this embodiment is:
[0038] S01: 2-5 parts of Sn powder and 1-3 parts of Zr powder are mixed, and then fully blended with 10-15 parts of sodium citrate solution to obtain a blended Sn-Zr agent;
[0039] S02: The blended Sn-Zr agent and the lanthanum-adjusted homogenizer are stirred and homogenized in a weight ratio of 5:2. After homogenization, the mixture is washed with water and dried to obtain a lanthanum homogenized modifier.
[0040] S03: The lanthanum homogeneous modifier is heat-treated at 175-185°C for 5-10 minutes, and then cooled to room temperature at a rate of 1-2°C / min to obtain a homogeneous denaturant.
[0041] The mass fraction of the sodium citrate solution in this embodiment is 10-15%; the homogenizing speed of the stirring homogenizing process is 750-850 r / min, and the homogenizing time is 20-30 min.
[0042] The preparation method of the lanthanum-regulated homogenizer of this embodiment is:
[0043] Add 3 to 5 parts of nano-silicon dioxide and 1 to 2 parts of ethanol solvent into 4 to 7 parts of sodium lignin sulfonate solution and mix thoroughly to obtain nano-silicon dioxide liquid;
[0044] 2-5 parts of nano-silica liquid, 3-4 parts of lanthanum nitrate solution, 1-2 parts of tetrabutyl titanate and 0.35-0.45 parts of nano-silica sol are ball-milled at a speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a lanthanum-adjusted homogenizer.
[0045] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 8-12%; the mass fraction of the lanthanum nitrate solution is 2-5%.
[0046] A method for preparing a high-strength and toughness soluble magnesium alloy in this embodiment comprises the following steps:
[0047] Step 1: Al, Ni, Cu and Mg are first smelted completely at 750°C, and then a homogenizing modifier is added and stirred and smelted for 25 to 30 minutes at a smelting speed of 450 to 500 r / min, and then argon is introduced for refining and degassing to obtain a smelt, which is poured into a mold to form an alloy ingot;
[0048] Step 2: The alloy ingot is placed in a lubricating liquid 3 to 5 times the volume of the alloy ingot for ultrasonic lubricity treatment. After the treatment, the ingot is washed with water and dried to obtain a body with improved wettability.
[0049] Step 3: The improved body of wettability is then subjected to a heat-enhanced improvement treatment, and after the treatment is completed, a heat-improved body is obtained;
[0050] Step 4: Extruding the heat-modified body to form the soluble magnesium alloy of the present invention, the extrusion temperature is 360° C., the extrusion ratio is 5-10, and the extrusion speed is 10 m / min.
[0051] The specific operation steps of the heat enhancement improvement treatment of this embodiment are:
[0052] First, perform primary treatment at a temperature of 320-350°C for 10-20 minutes, then reduce the temperature to 210-220°C at a rate of 2-4°C / min for secondary treatment for 20-30 minutes, and finally cool to room temperature at a rate of 1-3°C / min.
[0053] The ultrasonic power of the ultrasonic lubricity treatment in this embodiment is 350-400W, and the ultrasonic time is 20-30min.
[0054] The preparation method of the lubricating liquid of this embodiment is:
[0055] S11: placing the carbon nanotubes in a proton irradiation box for 5 to 10 minutes, with an irradiation power of 350 W, and then putting them into standby mode after the irradiation is completed;
[0056] S12: Then, 4 to 7 parts of irradiated carbon nanotubes, 2 to 5 parts of yttrium nitrate solution, 1 to 3 parts of silane coupling agent KH560 and 2 to 5 parts of sodium dodecylbenzene sulfonate solution are mixed thoroughly to obtain a lubricating liquid.
[0057] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 10-15%.
[0058] Example 1.
[0059] A high-strength and toughness soluble magnesium alloy of this embodiment includes the following raw materials in weight percentage:
[0060] Al 2%, Ni 1.5%, Cu 1.5%, homogeneous modifier 2%, and the balance is Mg.
[0061] The preparation method of the homogeneous denaturant of this embodiment is:
[0062] S01: Mix 2 parts of Sn powder and 1 to 3 parts of Zr powder, and then fully blend with 10 parts of sodium citrate solution to obtain a blended Sn-Zr agent;
[0063] S02: The blended Sn-Zr agent and the lanthanum-adjusted homogenizer are stirred and homogenized in a weight ratio of 5:2. After homogenization, the mixture is washed with water and dried to obtain a lanthanum homogenized modifier.
[0064] S03: The lanthanum homogeneous modifier is heat-treated at 175°C for 5 minutes, and then cooled to room temperature at a rate of 1°C / min to obtain a homogeneous modifier.
[0065] The mass fraction of the sodium citrate solution in this embodiment is 10%; the homogenizing speed of the stirring homogenizing process is 750 r / min, and the homogenizing time is 20 min.
[0066] The preparation method of the lanthanum-regulated homogenizer of this embodiment is:
[0067] Add 3-5 parts of nano-silicon dioxide and 1 part of ethanol solvent into 4 parts of sodium lignin sulfonate solution and mix thoroughly to obtain nano-silicon dioxide liquid;
[0068] 2 parts of nano-silica liquid, 3 parts of lanthanum nitrate solution, 1 part of tetrabutyl titanate and 0.35 parts of nano-silica sol are ball-milled at a speed of 1000 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a lanthanum-adjusted homogenizer.
[0069] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 8%; the mass fraction of the lanthanum nitrate solution is 2%.
[0070] A method for preparing a high-strength and toughness soluble magnesium alloy in this embodiment comprises the following steps:
[0071] Step 1: Al, Ni, Cu and Mg are first smelted completely at 750°C, and then a homogenizing modifier is added and stirred and smelted for 25 minutes at a smelting speed of 450r / min, and then argon is introduced for refining and degassing to obtain a smelt, which is poured into a mold to form an alloy ingot;
[0072] Step 2: The alloy ingot is placed in a lubricating liquid 3 times the volume of the alloy ingot for ultrasonic lubricity treatment. After the treatment, the ingot is washed with water and dried to obtain a body with improved wettability.
[0073] Step 3: The improved body of wettability is then subjected to a heat-enhanced improvement treatment, and after the treatment is completed, a heat-improved body is obtained;
[0074] Step 4: Extruding the heat-modified body to form the soluble magnesium alloy of the present invention, the extrusion temperature is 360° C., the extrusion ratio is 5, and the extrusion speed is 10 m / min.
[0075] The specific operation steps of the heat enhancement improvement treatment of this embodiment are:
[0076] First, perform the primary treatment at a temperature of 320°C for 10 minutes, then reduce the temperature to 210°C at a rate of 2°C / min for a secondary treatment for 20 minutes, and finally cool to room temperature at a rate of 1°C / min.
[0077] The ultrasonic power of the ultrasonic lubricity treatment in this embodiment is 350W, and the ultrasonic time is 20min.
[0078] The preparation method of the lubricating liquid of this embodiment is:
[0079] S11: placing the carbon nanotubes in a proton irradiation box for 5 minutes, with an irradiation power of 350 W, and then setting aside after the irradiation is completed;
[0080] S12: Then, 4 parts of irradiated carbon nanotubes, 2 parts of yttrium nitrate solution, 1 part of silane coupling agent KH560 and 2 parts of sodium dodecylbenzene sulfonate solution are mixed thoroughly to obtain a lubricating liquid.
[0081] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 10%.
[0082] Example 2.
[0083] A high-strength and toughness soluble magnesium alloy of this embodiment includes the following raw materials in weight percentage:
[0084] Al 4%, Ni 2.0%, Cu 2.0%, homogeneous modifier 4%, and the balance Mg.
[0085] The preparation method of the homogeneous denaturant of this embodiment is:
[0086] S01: Mix 5 parts of Sn powder and 3 parts of Zr powder, and then fully blend with 15 parts of sodium citrate solution to obtain a blended Sn-Zr agent;
[0087] S02: The blended Sn-Zr agent and the lanthanum-adjusted homogenizer are stirred and homogenized in a weight ratio of 5:2. After homogenization, the mixture is washed with water and dried to obtain a lanthanum homogenized modifier.
[0088] S03: The lanthanum homogeneous modifier is heat-treated at 185°C for 10 min, and then cooled to room temperature at a rate of 2°C / min to obtain a homogeneous modifier.
[0089] The mass fraction of the sodium citrate solution in this embodiment is 15%; the homogenizing speed of the stirring homogenizing process is 850 r / min, and the homogenizing time is 30 min.
[0090] The preparation method of the lanthanum-regulated homogenizer of this embodiment is:
[0091] Add 5 parts of nano-silicon dioxide and 2 parts of ethanol solvent into 7 parts of sodium lignin sulfonate solution and mix thoroughly to obtain nano-silicon dioxide liquid;
[0092] 5 parts of nano-silica liquid, 4 parts of lanthanum nitrate solution, 2 parts of tetrabutyl titanate and 0.45 parts of nano-silica sol were ball-milled at a speed of 1500 r / min for 1 hour. After the ball-milling was completed, the mixture was washed with water and dried to obtain a lanthanum-adjusted homogenizer.
[0093] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 12%; the mass fraction of the lanthanum nitrate solution is 5%.
[0094] A method for preparing a high-strength and toughness soluble magnesium alloy in this embodiment comprises the following steps:
[0095] Step 1: Al, Ni, Cu and Mg are first smelted completely at 750°C, and then a homogenizing modifier is added and stirred and smelted for 30 minutes at a smelting speed of 500r / min, and then argon is introduced for refining and degassing to obtain a smelt, which is poured into a mold to form an alloy ingot;
[0096] Step 2: The alloy ingot is placed in a lubricating liquid 5 times the volume of the alloy ingot for ultrasonic lubricity treatment. After the treatment, the ingot is washed with water and dried to obtain a body with improved wettability.
[0097] Step 3: The improved body of wettability is then subjected to a heat-enhanced improvement treatment, and after the treatment is completed, a heat-improved body is obtained;
[0098] Step 4: Extruding the heat-modified body to form the soluble magnesium alloy of the present invention, the extrusion temperature is 360° C., the extrusion ratio is 10, and the extrusion speed is 10 m / min.
[0099] The specific operation steps of the heat enhancement improvement treatment of this embodiment are:
[0100] First, perform the primary treatment at a temperature of 350°C for 20 minutes, then reduce the temperature to 220°C at a rate of 4°C / min for 30 minutes, and finally cool to room temperature at a rate of 3°C / min.
[0101] The ultrasonic power of the ultrasonic lubricity treatment in this embodiment is 400W, and the ultrasonic time is 30min.
[0102] The preparation method of the lubricating liquid of this embodiment is:
[0103] S11: placing the carbon nanotubes in a proton irradiation box for 10 minutes, with an irradiation power of 350 W, and then setting aside after the irradiation is completed;
[0104] S12: Then, 7 parts of irradiated carbon nanotubes, 5 parts of yttrium nitrate solution, 3 parts of silane coupling agent KH560 and 5 parts of sodium dodecylbenzene sulfonate solution are mixed thoroughly to obtain a lubricating liquid.
[0105] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 15%.
[0106] Example 3.
[0107] A high-strength and toughness soluble magnesium alloy of this embodiment includes the following raw materials in weight percentage:
[0108] Al 3%, Ni 1.8%, Cu 1.65%, homogeneous modifier 3%, and the balance Mg.
[0109] The preparation method of the homogeneous denaturant of this embodiment is:
[0110] S01: 3.5 parts of Sn powder and 2 parts of Zr powder are mixed, and then fully blended with 12.5 parts of sodium citrate solution to obtain a blended Sn-Zr agent;
[0111] S02: The blended Sn-Zr agent and the lanthanum-adjusted homogenizer are stirred and homogenized in a weight ratio of 5:2. After homogenization, the mixture is washed with water and dried to obtain a lanthanum homogenized modifier.
[0112] S03: The lanthanum homogeneous modifier is heat-treated at 180°C for 7.5 min, and then cooled to room temperature at a rate of 1.5°C / min to obtain a homogeneous modifier.
[0113] The mass fraction of the sodium citrate solution in this embodiment is 12.5%; the homogenizing speed of the stirring homogenizing treatment is 800 r / min, and the homogenizing time is 25 min.
[0114] The preparation method of the lanthanum-regulated homogenizer of this embodiment is:
[0115] Add 4 parts of nano-silicon dioxide and 1.5 parts of ethanol solvent into 5.5 parts of sodium lignin sulfonate solution and mix thoroughly to obtain nano-silicon dioxide liquid;
[0116] 3.5 parts of nano-silica liquid, 3.5 parts of lanthanum nitrate solution, 1.5 parts of tetrabutyl titanate and 0.40 parts of nano-silica sol were ball-milled at a speed of 1250 r / min for 1 hour. After the ball-milling was completed, the mixture was washed with water and dried to obtain a lanthanum-adjusted homogenizer.
[0117] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 10%; the mass fraction of the lanthanum nitrate solution is 3.5%.
[0118] A method for preparing a high-strength and toughness soluble magnesium alloy in this embodiment comprises the following steps:
[0119] Step 1: Al, Ni, Cu and Mg are first smelted completely at 750°C, and then a homogenizing modifier is added and stirred and smelted for 27 minutes at a smelting speed of 470 r / min, and then argon is introduced for refining and degassing to obtain a smelt, which is poured into a mold to form an alloy ingot;
[0120] Step 2: The alloy ingot is placed in a lubricating liquid 4 times the volume of the alloy ingot for ultrasonic lubricity treatment. After the treatment, the ingot is washed with water and dried to obtain a body with improved wettability.
[0121] Step 3: The improved body of wettability is then subjected to a heat-enhanced improvement treatment, and after the treatment is completed, a heat-improved body is obtained;
[0122] Step 4: Extruding the heat-modified body to form the soluble magnesium alloy of the present invention, the extrusion temperature is 360° C., the extrusion ratio is 7.5, and the extrusion speed is 10 m / min.
[0123] The specific operation steps of the heat enhancement improvement treatment of this embodiment are:
[0124] First, perform the primary treatment at a temperature of 335°C for 15 minutes, then reduce the temperature to 215°C at a rate of 3°C / min for a secondary treatment for 25 minutes, and finally cool to room temperature at a rate of 2°C / min.
[0125] The ultrasonic power of the ultrasonic lubricity treatment in this embodiment is 370W, and the ultrasonic time is 25min.
[0126] The preparation method of the lubricating liquid of this embodiment is:
[0127] S11: placing the carbon nanotubes in a proton irradiation box for 7.5 minutes, with an irradiation power of 350 W, and then putting them into standby mode after the irradiation is completed;
[0128] S12: 5.5 parts of irradiated carbon nanotubes, 3.5 parts of yttrium nitrate solution, 2 parts of silane coupling agent KH560 and 3.5 parts of sodium dodecylbenzene sulfonate solution are then mixed thoroughly to obtain a lubricating liquid.
[0129] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 12.5%.
[0130] Comparative Example 1.
[0131] The difference from Example 3 is that no homogenizing denaturant was added.
[0132] Comparative Example 2.
[0133] The difference from Example 3 is that no lanthanum-adjusted homogenizer treatment is used in the preparation of the homogenizing denaturant.
[0134] Comparative Example 3.
[0135] The difference from Example 3 is that no lanthanum nitrate solution is added in the preparation of the lanthanum-adjusted homogenizer.
[0136] Comparative Example 4.
[0137] The difference from Example 3 is that tetrabutyl titanate and nano-silica sol are not added in the preparation of the lanthanum-adjusted homogenizer.
[0138] Comparative Example 5.
[0139] The difference from Example 3 is that no nano-silica liquid is added in the preparation of the lanthanum-adjusted homogenizer.
[0140] Comparative Example 6.
[0141] The difference from Example 3 is that the S3 step is not used in the preparation of the homogenizing denaturant.
[0142] Comparative Example 7.
[0143] The difference from Example 3 is that the Sn-Zr agent blended in the preparation of the homogeneous modifier is replaced by Zr powder.
[0144] Comparative Example 8.
[0145] The difference from Example 3 is that no lubricating liquid treatment is used.
[0146] Comparative Example 9.
[0147] The difference from Example 3 is that no irradiated carbon nanotubes are added to the lubricating liquid.
[0148] Comparative Example 10.
[0149] The difference from Example 3 is that no yttrium nitrate solution and silane coupling agent KH560 are added to the lubricating liquid.
[0150] Comparative Example 11.
[0151] The difference from Example 3 is that no heat enhancement improvement treatment is used.
[0152] Comparative Example 12.
[0153] The difference from Example 3 is that the heat-enhanced improvement treatment does not use the secondary treatment of reducing the temperature to 215°C at a rate of 3°C / min, and the secondary treatment time is 25 minutes.
[0154] The products of Examples 1 to 3 and Comparative Examples 1 to 12 were subjected to conventional performance tests, and the test results are as follows
[0155]
[0156]
[0157] From Examples 1-3 and Comparative Examples 1-12, it can be seen that the compressive strength, flexural strength and elongation of the product can be improved in a coordinated manner, and the strength and toughness performance of the product are significantly improved;
[0158] Without adding homogenizing denaturant, without using lubricating liquid treatment and without using heat-enhanced improvement treatment, the performance of the product has a significant trend of deterioration. The three are used in combination to achieve synergistic effect.
[0159] In the preparation of the homogenizing denaturant, no lanthanum-adjusted homogenizing agent treatment was used, no lanthanum nitrate solution was added in the preparation of the lanthanum-adjusted homogenizing agent, no tetrabutyl titanate and nano-silica sol were added in the preparation of the lanthanum-adjusted homogenizing agent, and no nano-silicon dioxide liquid was added in the preparation of the lanthanum-adjusted homogenizing agent; the performance of the products all tended to deteriorate, and the lanthanum-adjusted homogenizing agent prepared by the method of the present invention had the most obvious performance effect of the product; in the preparation of the homogenizing denaturant, no S3 step treatment was used, and the Sn-Zr agent blended in the preparation of the homogenizing denaturant was replaced by Zr powder, and the performance of the product also showed a trend of deterioration, and only the homogenizing denaturant obtained by the method of the present invention had the most significant performance effect of the product;
[0160] The performance of the products showed a trend of deterioration when no irradiated carbon nanotubes were added to the lubricating liquid, no yttrium nitrate solution and silane coupling agent KH560 were added to the lubricating liquid, and the heat-enhanced improvement treatment was not subjected to secondary treatment at a rate of 3°C / min to 215°C, and the secondary treatment time was 25 minutes. Only when the lubricating liquid prepared by the method of the present invention and the specific heat-enhanced improvement treatment were used, the performance effect of the product was the most significant.
[0161] Continue to test the degradation performance of the product by placing it in a 3% KCL solution at a test temperature of 45°C;
[0162]
[0163]
[0164] From the above performance tests, it can be seen that the product of Example 3 has excellent degradation performance on the basis of high strength and high toughness. In 3% KCL solution, the test temperature is 45°C, and the corrosion performance is as high as 92.9 mg.cm -2 .h -1 above.
[0165] Place the product in a 2% water mist environment for 12 hours, then transfer to a temperature of 2°C to continue testing the product's strength and toughness performance;
[0166]
[0167]
[0168] It can be seen from Comparative Examples 1-12 and Examples 1-3;
[0169] The product of Example 3 still has excellent flexural strength and elongation properties in a humid and low-temperature environment, while the performance of the product shows an obvious trend of deterioration because no homogenizing denaturant is added, no lubricating liquid treatment is adopted, and no heat-enhanced improvement treatment is adopted. At the same time, the performance of the product shows a trend of deterioration when the homogenizing denaturant, lubricating liquid treatment, and heat-enhanced improvement treatment are prepared by different methods. Only the product raw materials prepared by the method of the present invention and the alloy products obtained by the process of the present invention have the most significant stability effects on the flexural strength and elongation properties.
[0170] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0171] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-strength and toughness soluble magnesium alloy, characterized in that: The following raw materials are included in weight percentage: Al 2-4%, Ni 1.5-2.0%, Cu 1.5-2.0%, homogeneous modifier 2-4%, and the balance Mg.
2. A high-strength and toughness soluble magnesium alloy according to claim 1, characterized in that: The preparation method of the homogenizing denaturant is: S01: 2-5 parts of Sn powder and 1-3 parts of Zr powder are mixed, and then fully blended with 10-15 parts of sodium citrate solution to obtain a blended Sn-Zr agent; S02: The blended Sn-Zr agent and the lanthanum-adjusted homogenizer are stirred and homogenized in a weight ratio of 5:
2. After homogenization, the mixture is washed with water and dried to obtain a lanthanum homogenized modifier. S03: The lanthanum homogeneous modifier is heat-treated at 175-185°C for 5-10 minutes, and then cooled to room temperature at a rate of 1-2°C / min to obtain a homogeneous denaturant.
3. A high-strength and toughness soluble magnesium alloy according to claim 2, characterized in that: The mass fraction of the sodium citrate solution is 10-15%; the homogenizing speed of the stirring homogenizing treatment is 750-850 r / min, and the homogenizing time is 20-30 min.
4. A high-strength and toughness soluble magnesium alloy according to claim 2, characterized in that: The preparation method of the lanthanum-regulated homogenizer is: Add 3 to 5 parts of nano-silicon dioxide and 1 to 2 parts of ethanol solvent into 4 to 7 parts of sodium lignin sulfonate solution and mix thoroughly to obtain nano-silicon dioxide liquid; 2-5 parts of nano-silica liquid, 3-4 parts of lanthanum nitrate solution, 1-2 parts of tetrabutyl titanate and 0.35-0.45 parts of nano-silica sol are ball-milled at a speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a lanthanum-adjusted homogenizer.
5. A high-strength and toughness soluble magnesium alloy according to claim 4, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 8-12%; the mass fraction of the lanthanum nitrate solution is 2-5%.
6. A method for preparing a high-strength and toughness soluble magnesium alloy as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Al, Ni, Cu and Mg are first smelted completely at 750°C, and then a homogenizing modifier is added and stirred and smelted for 25 to 30 minutes at a smelting speed of 450 to 500 r / min, and then argon is introduced for refining and degassing to obtain a smelt, which is poured into a mold to form an alloy ingot; Step 2: The alloy ingot is placed in a lubricating liquid 3 to 5 times the volume of the alloy ingot for ultrasonic lubricity treatment. After the treatment, the ingot is washed with water and dried to obtain a body with improved wettability. Step 3: The improved body of wettability is then subjected to a heat-enhanced improvement treatment, and after the treatment is completed, a heat-improved body is obtained; Step 4: Extruding the heat-modified body to form the soluble magnesium alloy of the present invention, the extrusion temperature is 360° C., the extrusion ratio is 5-10, and the extrusion speed is 10 m / min.
7. The method for preparing a high-strength and toughness soluble magnesium alloy according to claim 6, characterized in that: The specific operation steps of the heat enhancement improvement treatment are: First, perform primary treatment at a temperature of 320-350°C for 10-20 minutes, then reduce the temperature to 210-220°C at a rate of 2-4°C / min for secondary treatment for 20-30 minutes, and finally cool to room temperature at a rate of 1-3°C / min.
8. The method for preparing a high-strength and toughness soluble magnesium alloy according to claim 6, characterized in that: The ultrasonic power of the ultrasonic lubricity treatment is 350-400W, and the ultrasonic time is 20-30min.
9. The method for preparing a high-strength and toughness soluble magnesium alloy according to claim 6, characterized in that: The preparation method of the lubricating liquid is: S11: placing the carbon nanotubes in a proton irradiation box for 5 to 10 minutes, with an irradiation power of 350 W, and then putting them into standby mode after the irradiation is completed; S12: Then, 4 to 7 parts of irradiated carbon nanotubes, 2 to 5 parts of yttrium nitrate solution, 1 to 3 parts of silane coupling agent KH560 and 2 to 5 parts of sodium dodecylbenzene sulfonate solution are mixed thoroughly to obtain a lubricating liquid.
10. The method for preparing a high-strength and toughness soluble magnesium alloy according to claim 9, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 10-15%.
